Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Les théories scientifiques ont-elles un sexe? : actes du colloque - Decerf, Anne (Éditions d'Acadie, 1991)
Keywords: amériques; approches et analyses; canada; cours; cycles supérieurs; discipline; fem9000; inégalités; régions géographiques; sciences; sexisme; systèmes d'oppressions

Le féminin, un espace autre pour le désir - Bergeron, Danielle (Santé mentale au Québec, 1990)
La littérature psychanalytique s'est développée autour du concept d'un espace pour le désir structuré selon le modèle des rapports du garçon à sa mère. La clinique de la féminité, concurremment avec l'apport historique du féminisme, découvre-t-elle un espace autre pour le désir féminin ? La psychotique pour qui la place du père est restée vide dans la parole de la mère, refuse la Loi comme représentant de l'autorité sociale. Quant à l'hystérique, elle ne se fie pas au Père comme rempart contre le vide qui se profile derrière les Lois et les croyances des hommes. À sa façon, le féminisme reprend, en les projetant sur la scène sociale, ces positions de refus psychotique et de contestation hystérique et requiert de nouvelles formes de vie sociale qui s'articulent à l'espace esthétique dont les femmes ont besoin pour vivre comme citoyennes à part entière.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; patriarcat; psychanalyse; ressource en ligne; santé; sciences; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques